Clinical proteomics in obstetrics and neonatology. (February 2014) - Klein, Julie; Buffin-Meyer, Benedicte; Mullen, William; Carty, David M; Delles, Christian; Vlahou, Antonia; Mischak, Harald; Decramer, Stéphane; Bascands, Jean-Loup; Schanstra, Joost P
<x xml:space="preserve">Abstract</x> Clinical proteomics has been applied to the identification of biomarkers of obstetric and neonatal disease. We will discuss a number of encouraging studies that have led to potentially valid biomarkers in the context of Down's syndrome, preterm birth, amniotic infections, preeclampsia, intrauterine growth restriction and obstructive uropathies. Obtaining noninvasive biomarkers (e.g., from the maternal circulation, urine or cervicovaginal fluid) may be more feasible for obstetric diseases than for diseases of the fetus, for which invasive methods are required (e.g., amniotic fluid, fetal urine). However, studies providing validated proteomics-identified biomarkers are limited. Efforts should be made to save well-characterized samples of these invasive body fluids so that many valid biomarkers of pregnancy-related diseases will be identified in the coming years using proteomics based analysis upon adoption of 'clinical proteomics guidelines'.